(untitled) (Revista Brasileira Multidisciplinar, 2023)
This study aimed to identify the types of clinical pharmaceutical services that are being developed, as well as the respective benefits produced for patients on dialysis. For that, the methodology of integrative review of scientific literature of the last 10 years was adopted. Studies published in Pubmed were recruited. After analyzing the scientific production according to the inclusion and exclusion criteria, five articles were retrieved. Several types of clinical pharmaceutical services were identified, with special emphasis on pharmacotherapeutic follow-up, which corresponded to the most mentioned category. Pharmacotherapy review services, drug reconciliation, user counseling and assessment / promotion of treatment adherence were also developed. Pharmaceutical care for dialysis patients resulted in increased satisfaction, quality of life, treatment adherence, hemoglobin and plasma calcium. Benefits were also found in reducing the following parameters: plasma phosphorus, interdialytic weight gain and blood pressure. Thus, clinical and humanistic contributions were found in the development of pharmaceutical care for patients on dialysis.